Iklim kerja yang etis dan intensi melakukan whistleblowing - Nur, Ahmad Lidiono; Sulistyaningsih, Endang; Nilawati, Levi (Jurnal Manajemen Maranatha, 2024)
The purpose of this study is to examine the impact of an ethical work environment on the intention to report wrongdoing, with job satisfaction and self-efficacy as mediating factors, drawing from the Theory of Planned Behavior. The research was conducted at a state-owned bank, employing purposive sampling to gather data from 210 banking employees in Jakarta, Indonesia. Hypothesis testing utilized Structural Equation Modeling (SEM) with the Lisrel 8.80 program. The findings indicate that an ethical work climate has a positive influence on job satisfaction, self-efficacy, and whistleblowing intention. However, job satisfaction exerts a negative impact on whistleblowing intention, and therefore does not mediate the relationship between the ethical work environment and whistleblowing intention. Meanwhile, self-efficacy positively affects whistleblowing intention, but similarly does not mediate the relationship with ethical work climate. This study demonstrates that the intention to behave is the primary determinant of a person's actions and is not significantly influenced by the two tested mediating variables, following the Theory of Planned Behavior.